An atypical deletion of the Williams–Beuren syndrome interval implicates genes associated with defective visuospatial processing and autism. Issue 2 (13th September 2006) - Edelmann, Lisa; Prosnitz, Aaron; Pardo, Sherly; Bhatt, Jahnavi; Cohen, Ninette; Lauriat, Tara; Ouchanov, Leonid; González, Patricia J; Manghi, Elina R; Bondy, Pamela; Esquivel, Marcela; Monge, Silvia; et al.
Abstract : Background: During a genetic study of autism, a female child who met diagnostic criteria for autism spectrum disorder, but also exhibited the cognitive–behavioural profile (CBP) associated with Williams–Beuren syndrome (WBS) was examined. The WBS CBP includes impaired visuospatial ability, an overly friendly personality, excessive non-social anxiety and language delay. Methods: Using array-based comparative genomic hybridisation (aCGH), a deletion corresponding to BAC RP11-89A20 in the distal end of the WBS deletion interval was detected. Hemizygosity was confirmed using fluorescence in situ hybridisation and fine mapping was performed by measuring the copy number of genomic DNA using quantitative polymerase chain reaction. Results: The proximal breakpoint was mapped to intron 1 of GTF2IRD1 and the distal breakpoint lies 2.4–3.1 Mb towards the telomere. The subject was completely hemizygous for GTF2I, commonly deleted in carriers of the classic ∼1.5 Mb WBS deletion, and GTF2IRD2, deleted in carriers of the rare ∼1.84 Mb WBS deletion. Conclusion: Hemizygosity of the GTF2 family of transcription factors is sufficient to produce many aspects of the WBS CBP, and particularly implicate the GTF2 transcription factors in the visuospatial construction deficit. Symptoms of autism in this case may be due to deletion of additional genes outside the typical WBS interval or remote effects on gene expression at other loci.